MODIFIKASI DAN KARAKTERISASI MORDENIT TERAKTIVASI HCl DENGAN (3-AMINOPROPIL)TRIMETOKSISILAN UNTUK ADSORPSI ION Cu(II) - , PRADIKA WIDIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Modification and characterization of HCl-activated mordenite with (3-Aminopropyl)trimethoxysilane (3-APTMS) for adsorption of Cu(II) ions have been carried out. Four grams of mordenite (MOR) was activated by 20 mL of 6 M HCl solution for 30 and 120 min. to produce MOR-30 and MOR-120 samples. The mordenite samples were then modified with 3-APTMS by grafting method to produce MOR/NH2, MOR-30/NH2 and MOR-120/NH2 samples. Activity of the mordenite samples as an adsorbent was analyzed by the adsorption of Cu(II) ions in CuSO4 solution. Those samples were then analyzed using Fourier transform infrared (FT-IR) spectrophotometer, X-ray diffractrometer (XRD) and atomic absorption spectrophotometer (AAS) instrument. The results showed that the 6 M HCl solution treatment increased Si/Al ratio of the MOR samples. The Si/Al ratio of MOR, MOR-30, MOR-120 sample was 5.35, 16.33 and 18.26, respectively. The FT-IR spectra of the modified mordenite samples showed the absorption peaks at 2900 â 3000 cm-1 as streching vibration of C-H sp3 and was strengthen with 1460 cm-1 as its bending vibration. The highest adsorption concentration toward the Cu(II) was shown by the MOR-120/NH2 (8.43 mg g-1). The adsorption kinetic of Cu(II) ions by the MOR-120/NH2 followed the pseudo-second order model with the adsorption rate constant (k) of 1.5 x 10-1 g mg-1 min-1, followed the adsorption isotherm model of Langmuir with the adsorption capacity of 36.232 mg g-1 and the adsorption energy of 22.612 kJ mol-1.